Modeling of asymmetric division of somatic cell in protoplasts culture of higher plants - S. I. Kondratenko; T. P. Pasternak; O. P. Samovol; O. M. Mogilna; O. V. Sergienko (Regulatory Mechanisms in Biosystems, 2020)
The key result of the work is the selection of factors for the cultivation of protoplasts of higher plants in vitro, which allowed induction of asymmetrical cell division during the first cell cycle phase. Gibberellin has been proved to be one of the main cofactors of asymmetric division of plant cells. The objects of research were plants of the following cultivars aseptically grown in hormone-free MS medium: tobacco (Nicotiana tabacum L.), SR-1 line; Arabidopsis thaliana var. columbia (L.) Heynh; potato (Solanum tuberosum L.), Zarevo cultivar; cultivated white head cabbage (Brassica oleraceae var. capitata L.) of the following varieties: Kharkivska zymnia, Ukrainska osin, Yaroslavna, Lika, Lesya, Bilosnizhka, Dithmarscher Früher, Iyunskarannya; rape (Brassica napus L.) of Shpat cultivar; winter radish (Raphanus sativus L.) of Odessa-5 cultivar. In experiments with mesophilic and hypocotyl protoplasts of the above-mentioned plant species it has been proved that short-term osmotic stress within 16–18 hours being combined with subsequent introduction of high doses of gibberellin GK3 (1 mg/L) into the modified liquid nutrient media TM and SW led to the occurrence of pronounced morphological traits of cytodifferentiation already at the initial stages of the development of mitotically active cells in a number of higher plants. Meanwhile, in all analyzed species, there was observed the division of the initial genetically homogeneous population of mitotically active cells into two types of asymmetric division: by the type of division of the mother cell into smaller daughter cells and by the type of the first asymmetric division of the zygotic embryo in planta. In this case, the first type of asymmetric division occurred during unusual cytomorphism of the mother cells: a pronounced heart-shaped form even before the first division, which is inherent in the morphology of somatic plant embryo in vitro at the heart-shaped stage. A particular study of the effect of osmotic stress influencing protoplasts of various cultivars of white cabbage, isolated from hypocotyls of 7–9 day etiolated seedlings, revealed quite a typical consistent pattern: the acquisition and maintenance of the axis of symmetry in growing microcolonies occurred without extra exogenous gibberellin (GK3), which was added to the nutrient medium earlier. While analyzing the effect of growth regulators on the formation of microcolonies with traits of structural organization, the conclusion was made regarding the commonality of the revealed morphogenetic reactions of cells within the culture of protoplasts of higher plants in vitro with similar reactions studied earlier on other plants, both in vitro and in planta. Modeling of asymmetric cell division in protoplast culture in vitro has become possible by carrying out a balanced selection of growth regulators as well as their coordinated application through time along with changes in osmotic pressure of a nutrient medium.